TEKNOLOGI PENYULINGAN MINYAK SEREH WANGI SKALA KECIL DAN MENENGAH DI JAWA BARAT - Aviasti Anwar; Nugraha Nugraha; Aswardi Nasution; Reni Amaranti (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Citronella oil processing industry made a major contribution in improving the economy of the community, especially involve businesses, that is farmers and industrialists. Issues contained in the refining of citronella oil, one of which is requiring relatively large initial costs. The main objective of this research is to create model of industry system for citronella oil processing, small and medium scale so as to optimize the potential and available resources. The first step taken was identify the technologies used, determine the scale of production, how to manage and determine the variables considered to be a critical factor in the refining industry of citronella oil . As of this paper is made, a team of researchers have done several times a survey to see manufactured machine for citronella refining and compare the right technology so citronella oil produced is optimal In addition, researchers conducted a survey to a distillery that uses machine examined, to see firsthand how the refining machine. Stages of research conducted in a structured from preliminary studies, the formulation of the problem and determining the purpose of research, literature studies, define the steps of research, collection of data required, and the design of industrial systems, implementation models, and the final analysis of the results of implementation and improvement models.